The effectiveness of whatsapp in enhancing english language proficiency among UTAR undergraduates - Sandhiya, Achutan (2021)
Despite the large variety of languages spoken worldwide, English is still the most often used language online. Students in higher education are actively using social networks, which is frequently acknowledged. The goal of this report is to examine the effectiveness of WhatsApp in enhancing English language proficiency among UTAR undergraduates. Research objectives in this research are to investigate the effectiveness of WhatsApp in enhancing undergraduate’s English language proficiency and to critically analyze on how WhatsApp can enhance English language proficiency among UTAR undergraduates. A mixed-method technique, also referred to as using both quantitative and qualitative methods, are used in this study. The research’s instruments included a survey questionnaire as well as an open-ended interview questions. The first highest mean and SD is “I was able to convey any information easily by using WhatsApp” (M = 3.4, SD = 2.921). Using WhatsApp, students can instantly share knowledge or any other news with their friends and professors. Students may learn more about English and improve their command of the language in this way. The majority of the five participants, based on their replies, agreed that WhatsApp is an excellent platform for them to study and improve their English language proficiency. It is advised to conduct the study with a larger sample so that the researcher can obtain more insightful study data as well as a better grasp of the data.